Von “Inländern” und “Barbaren”. Identitäts- und Alteritätskonzepte bei Ilse Aichinger und Konstantinos Kavafis (Studia austriaca, 2013)
In their texts Ilse Aichinger and Konstantinos Kavafis adopt a perspective from which the conceptions of identity and otherness can be questioned and their interrelationship reconsidered. The binary opposition between “Us” and the “Other” is thus undermined and its dimension as a discursive construction becomes apparent. Both Aichinger and Kavafis do not focus on the “Other” when writing about “Barbarians”; they rather question the conception of “Us”. The subversive value of these texts lies in this very questioning of a homogeneous and clearly drawn conception of identity.